The essence of specialized knowledge used in the investigation of criminal offenses against justice - Grytsenko, Volodymyr (Archives of Criminology and Forensic Sciences, 2024)
Given the importance of special knowledge in solving tactical tasks of investigation and tasks of criminal proceedings, the purpose of the article is to define the concept, essence and typical forms of special knowledge used in the investigation of criminal offenses against justice. Based on the generalization of theoretical approaches to the essence of specialized knowledge, the author substantiates the thesis that over time, the author’s definitions have become quantitatively more complex and qualitatively improved. It is found that today the use of specialized knowledge in the field of craft in criminal proceedings has become unconventional, and the pre-trial investigation authorities give the prerogative to those forms which are based on scientifically sound provisions, although at one time it was craft knowledge and skills which became the basis for the development of scientific theories and concepts. It is found that the most common form of using specialized knowledge in the investigation of criminal offenses against justice is to engage an expert to conduct an examination. A number of other conceptual conclusions are also formulated.